Corporate Contributions: Altruistic or For-Profit? - Fry, Louis W.; Keim, Gerald D.; Meiners, Roger E. (Academy of Management Journal, 1982)
Existing literature has focused on three rationales for corporate philanthropy: through-the-firm giving, corporate statesmanship, and profit motivated giving. The profit motivation argument was examined by determining the relationship between giving and advertising expenditures. The results indicate that contributions are motivated by profit considerations that influence both advertising expenditures and corporate giving.